Educational Methods Used And Subject Matter Area Delivered By Extension Agents in South Karnataka, India - Rama Radhakrishna; V. Veerabhadraiah (Journal of Applied Communications, 1992)
The Primary purpose of this study was to determine the frequency of use of educational methods and subject matter delivered by Extensionagents in South Karnataka, India.